Exploring Lexical Demands in the IELTS Reading Test: A Corpus-Based Analysis on the Academic IELTS - Nur Rahma Yuli Rusmita; Restu Santyarini (Perkumpulan Cendekia Muda Kreatif Indonesia, 2025)
Acquiring knowledge of vocabulary is essential for learning a second language, since vocabulary serves as the foundation for the language. In the Academic IELTS, one of the most common English proficiency tests, vocabulary is highly crucial to master, especially in reading. This study uses a corpus-based methodology with AntWordProfiler software to analyze 18 IELTS books (Cambridge Practice Tests for IELTS 1996-2023) and identify 246 high-frequency AWL words. Data reduction techniques produce 217 words and filtered into 172 distinct word families. The findings aim to enhance IELTS exam preparation by providing insights into AWL vocabulary, potentially guiding future research to include broader word lists for a more comprehensive understanding.